Preparation method and application of nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst
By introducing phosphomolybic acid on Co-MOF and calcining, nano bowl-shaped molybdenum-doped CoP catalysts are prepared, and surface functionalization is carried out, the problems of high cost of precious metal catalysts and insufficient adsorption capacity of CoP catalysts are solved, achieving high efficiency catalytic properties of electrochemical water decomposition.
Patent Information
- Application Number
- CN202411427012.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-07
AI Technical Summary
In the existing electrochemical decomposition of water hydrogen production technology, the high cost and low reserves of precious metal catalysts limit their large-scale application, and the pure CoP catalyst has insufficient adsorption capacity to adsorb intermediates at active sites, which limits its catalytic performance. Play.
Using nano-bowl-shaped molybdenum-doped metal cobalt phosphide catalyst, Mo-CoP is prepared by introducing phosphomolybic acid on Co-MOF and calcining. Combined with surface functionalization, the electronic structure and morphology of the catalyst are optimized, and catalytic activity and medium are improved. Transmission efficiency.
It significantly improves the reactivity and electrochemical properties of the catalyst, reduces the kinetic energy barrier of the water decomposition reaction, and achieves high catalytic efficiency and stability. It is suitable for hydrogen absorption and oxygen absorption reactions of electrolyzed water.
Smart Images

Figure CN119265620A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano-catalytic materials, and in particular to a preparation method and application of a nano-bowl-shaped molybdenum-doped metal cobalt phosphide catalyst. Background Art
[0002] Hydrogen is an ideal clean energy carrier due to its sustainability and eco-friendly characteristics. Electrochemical water decomposition to produce hydrogen is a promising green hydrogen production technology. The water splitting reaction includes the cathode hydrogen evolution reaction (HER) and the anode oxygen evolution reaction (OER), both of which are limited by slow kinetics. In order to accelerate the rate of water decomposition, a catalyst is needed to reduce the reaction energy barrier. Platinum-based catalysts can effectively reduce the HER overpotential, and iridium-based or ruthenium-based material oxides are excellent catalysts for reducing the OER overpotential. However, the high cost and low reserves of precious metal catalysts limit their large-scale application. It is urgent to explore low-cost and highly active water electrolysis catalysts.
[0003] Cobalt-based materials have become ideal materials for building efficient electrocatalysts due to their excellent catalytic performance and abundant reserves. In particular, cobalt phosphide catalysts, in which the metal Co and P sites are proton and hydride acceptors, respectively, have both HER and OER catalytic activity. However, the performance of pure CoP catalysts is still not enough for practical applications, especially the adsorption capacity of active sites for adsorbed intermediates cannot be effectively regulated, which limits the performance of their catalytic performance.
[0004] Heteroatom doping can adjust the electronic structure of materials, optimize adsorption energy, and reduce reaction kinetic energy barriers. For example, patent number CN202110038314 reports a Ru-doped cobalt phosphide nanoarray catalyst, which significantly enhances the hydrogen evolution performance of CoP. However, as a precious metal, Ru is also limited in its large-scale application. Therefore, it is of great significance to develop non-precious metal-doped cobalt phosphide catalysts. In addition, the nanostructure of the catalyst also affects its catalytic performance. Generally speaking, hollow catalysts allow full contact between the active sites and the electrolyte, while facilitating medium transmission during the reaction. Therefore, hollow catalysts are highly favored.
[0005] Based on this, this patent developed a molybdenum-doped cobalt phosphide nanobowl catalyst and studied its hydrogen and oxygen evolution activities. The results show that the valence state of Co in cobalt phosphide increased due to molybdenum doping, which improved the intrinsic catalytic activity of the catalyst. At the same time, the nanobowl-shaped structure ensures rapid medium transmission, and the activity of the prepared Mo-CoP catalyst is significantly better than that of the undoped catalyst, indicating the important role of doping strategy in performance improvement. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a preparation method of a nano-bowl molybdenum-doped metal cobalt phosphide catalyst and its application.
[0007] The technical solution of the present invention is: a method for preparing a nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst, comprising the following steps:
[0008] S1. Preparation of CoMo-MOF
[0009] At room temperature, phosphomolybdic acid and cobalt acetate were mixed and dissolved in DMF at a ratio of 177.02 mg:40 mL. After the dissolution was completed, 328.4 mg of 0.3-0.4 mol / L 2-methylimidazole was poured in, stirred for 20-24 hours, and the product was collected by centrifugation, and washed alternately with deionized water and anhydrous ethanol for 2-4 times, and dried to obtain CoMo-MOF;
[0010] S2. Preparation of Mo-CoP
[0011] The CoMo-MOF obtained in step S1 is moved into a tubular furnace, and a quartz crucible containing anhydrous sodium hypophosphite is placed on the upstream side of the tubular furnace. The temperature is increased to 340-360°C at a heating rate of 1.5-2.5°C / min under an inert atmosphere and kept for 2 hours, and then cooled to obtain a nano-bowl-shaped molybdenum-doped metal cobalt phosphide catalyst, recorded as Mo-CoP.
[0012] Further, in step S1, the mass ratio of phosphomolybdic acid to cobalt acetate is 99-101:76.02-78.02;
[0013] Description: The experimental results show that the Mo-CoP obtained by mixing phosphomolybdic acid and cobalt acetate in the above ratio has better structural stability, which is beneficial to the catalytic performance. At the same time, the obtained Mo-CoP has a higher specific surface area and porosity, which is beneficial to the adsorption and mass transfer of substances, exhibits excellent electrochemical properties, and has a better effect on improving the reaction activity of the catalyst.
[0014] Further, in step S2, the mass ratio of the CoMo-MOF to anhydrous sodium hypophosphite is 1:10;
[0015] Note: CoMo-MOF and anhydrous sodium hypophosphite in the above ratio are conducive to the formation of a suitable crystal phase and microstructure, which can effectively improve the electrochemical properties of molybdenum-doped metal cobalt phosphide, such as catalytic activity, electrical conductivity, etc.; and this ratio is conducive to controlling the composition and morphology of molybdenum-doped metal cobalt phosphide, thereby optimizing its performance.
[0016] Further, in step S2, the inert atmosphere is nitrogen or argon;
[0017] Note: The use of the above-mentioned inert atmosphere can avoid the influence of impurities, thereby reducing the impact of external factors on the catalytic performance of Mo-CoP.
[0018] Furthermore, in step S1, the centrifugal speed is 5000-5500 r / min, the centrifugal time is 5-10 min; the drying temperature is 55-65° C., and the drying time is 5-6 h;
[0019] Note: The CoMo-MOF obtained under the above parameters has less impurities and higher purity.
[0020] Further, in step S2, the nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst is subjected to surface functionalization treatment;
[0021] The method of the surface functionalization treatment is:
[0022] 1) Microporous treatment of carrier: insert the polystyrene microsphere template into a solution containing 0.3-0.7% azobisisobutyronitrile and the remainder of vinyl monomer, heat and polymerize at 40-50°C for 3-5h, then etch with a pore etchant for 25-40min, wash with ether and dry to obtain a polystyrene particle carrier with three-dimensional pores on the surface;
[0023] 2) Composite treatment: the nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst is mixed with tetrahydrofuran in a mass ratio of 5 to 30:7 to obtain a mixture, and 5 to 10 wt.% of hydrogen peroxide is added to the mixture for sulfonation for 10 to 15 minutes, and the loaded particles are obtained after filtration and vacuum drying, and finally the loaded particles are deposited in the three-dimensional pores on the surface of the polystyrene particle carrier by magnetron sputtering under an argon protective atmosphere, and the treated nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst is obtained by homogenization; wherein the vacuum degree of magnetron sputtering is 1.5×10 -1 ~1.8×10 -1 Pa, working pressure is 15-20Pa, sputtering power is 40-80W, argon flow rate is 30-100sccm, deposition temperature is 200-300℃, sputtering time is 1-20min; vacuum drying parameters are: vacuum degree: 100-133Pa, vacuum temperature is 65-85℃, drying time is 15-30min;
[0024] Description: Surface functionalization effectively improves the stability and reusability of nano-molybdenum-doped metal cobalt phosphide catalysts; polystyrene microspheres are used as templates to form a three-dimensional pore structure through polymerization and etching. The copolymerization of azobisisobutyronitrile and vinyl monomers can form a polymer skeleton on the template. The pore etchant can selectively remove the polystyrene microsphere template, leaving a three-dimensional pore structure; stable polystyrene particles are used as carriers to increase the specific surface area and mechanical strength of the catalyst, thereby enhancing its anti-deactivation and reusability.
[0025] Sulfonation treatment can introduce sulfonic acid groups on the surface of molybdenum-doped metal cobalt phosphide powder. These groups can serve as active sites to improve the adsorption capacity and catalytic activity of the catalyst. Hydrogen peroxide oxidizes the hydroxyl groups (-OH) in tetrahydrofuran (THF) molecules, thereby introducing sulfonic acid groups (-SO3H). The introduction of sulfonic acid groups can increase the hydrophilicity of the material, improve its interaction with metals or other materials, and help form a more stable catalyst structure, thereby enhancing the interaction between the catalyst and the carrier. The layered three-dimensional structure can improve the electrochemical performance and facilitate the transmission of ions and electrons.
[0026] Tetrahydrofuran has a relatively low boiling point and is easy to remove during the experiment, which helps to shorten the experimental time and reduce pollution. At the same time, as a solvent, tetrahydrofuran has low viscosity and low surface tension, which helps mixing and stirring, thereby accelerating the reaction. It can help molybdenum-doped metal cobalt phosphide powder to be better dispersed and impregnated on the surface of the polystyrene particle carrier, thereby improving the loading efficiency and uniformity of the catalyst. Subsequent sulfonation treatment can introduce hydrophilic groups to further stabilize this layered three-dimensional nanobowl-shaped structure and enhance its catalytic performance. The parameters in the vacuum drying process can ensure that the material will not be thermally decomposed or oxidized during the drying process, while effectively removing moisture.
[0027] Furthermore, it is characterized in that the channel etchant comprises, by mass percentage, 25-40% lime, 10-15% sodium sulfate, 5-10% zinc gluconate, 5-8% divinylbenzene, and the balance tannic acid;
[0028] Description: As a strong base, lime can adjust the pH value of the etchant, increase the etching rate, and help improve the pore morphology, increase the etching rate, enhance the etching uniformity, and facilitate removal; sodium sulfate can increase the viscosity of the etchant, help the etchant to be evenly coated on the surface of the polystyrene particle carrier, thereby improving the uniformity of etching; zinc gluconate, as a stabilizer, helps to control the full action during the etching process and improve the uniformity of etching; divinylbenzene can form a cross-linked structure between polystyrene molecular chains and increase the three-dimensional network structure of the polymer, thereby improving mechanical strength and chemical corrosion resistance; as a natural polymer compound, tannic acid may form a complex with the carrier surface or the intermediate product produced by etching through its polyphenol structure, which helps to remove the by-products after etching and may also provide a certain etching selectivity.
[0029] Furthermore, the homogenization method is: first increase the temperature to 70-80°C at a rate of 1-3°C / s, then maintain a constant temperature for 1.5-2h, and simultaneously apply a magnetic field during the constant temperature treatment. The magnetic field strength is 0.3-1T, and the treatment time is 1-1.5h. Then, cool down to 45-50°C at a rate of 0.05-0.1°C / s, remove the homogenization furnace and continue to cool to 25-30°C.
[0030] Note: By controlling the heating rate and magnetic field treatment simultaneously, the microstructure of the catalyst can be optimized, and its dispersion on the carrier surface and the exposure of active sites can be improved. Magnetic field treatment under constant temperature conditions can promote the orderly arrangement of catalyst particles in the carrier pores through magnetocaloric effect and magnetically induced self-assembly, thereby enhancing the stability and catalytic performance of the catalyst.
[0031] The present invention also provides an application of a nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst, wherein the nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst is applied to a process of catalyzing the electrolysis of water to absorb hydrogen and oxygen.
[0032] Furthermore, the method of catalyzing the electrolysis of water using the nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst is as follows: the electrolyte is a 1 mol / L KOH aqueous solution, a graphite rod is used as a counter electrode, a saturated calomel electrode is used as a reference electrode, and a surface-treated nano bowl molybdenum-doped metal cobalt phosphide is fixed with a glassy carbon fixture as a working electrode. The current density is 50 mA / cm2, the electrolysis time is 20 min, and then stopped for 20 min, the two are performed alternately, and the voltage change curve over time is recorded.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] (1) The present invention introduces phosphomolybdic acid into Co-MOF and prepares a series of Mo-doped CoP catalysts Mo-CoP for HER and OER by phosphating and calcining. The experimental results show that appropriate phosphomolybdic acid can improve the reaction activity of the catalyst. 200 -CoP catalyst exhibits an overpotential of 299 mV in HER, Mo 100 The -CoP catalyst exhibits an overpotential of 300 mV in OER.
[0035] (2) The addition of molybdic acid changes the structural morphology of the precursor and promotes the formation of CoP species during the calcination process. The prepared Mo-CoP catalyst inherits the bowl-shaped morphology of the MOF precursor, which is beneficial to mass transfer during the catalytic process. In addition, the presence of Mo regulates the electronic structure of the material and induces the production of more Co 3+ , which improves the intrinsic activity of the catalytic sites; the improvement in catalyst activity can be attributed to the presence of more Co 3+ The active catalytic sites and the nano bowl-shaped structure for promoting medium transmission, the preparation method is simple, the raw materials are easily available, and the particle size distribution of the obtained product particles is uniform.
[0036] (3) The present invention performs surface functionalization treatment on nano bowl-shaped molybdenum-doped metal cobalt phosphide powder, and further improves the electrochemical performance by introducing a polystyrene particle carrier with three-dimensional pores, which is beneficial to the transmission of ions and electrons. The polystyrene particles serve as carriers to increase the specific surface area and mechanical strength of the catalyst, thereby enhancing its anti-deactivation and reusability. Tetrahydrofuran is used to promote better dispersion and impregnation of the nano bowl-shaped molybdenum-doped metal cobalt phosphide powder on the surface of the polystyrene particle carrier, thereby improving the loading efficiency and uniformity of the powder. The hydrophilic group is introduced through sulfonation treatment to enhance the stability of the catalyst, thereby effectively improving the catalytic ability and catalytic effect of the nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst for electrolysis of water. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 (a) is the XRD pattern of Co-MOF and CoMo-MOF-M; (b) is the XRD pattern of Co-MOF-350 and Mo M -XRD pattern of CoP@NC;
[0038] Figure 2 The (ah) in the figure is Co-MOF, CoMo-MOF, Co-MOF-350 and Mo M -SEM image of CoP@NC;
[0039] Figure 3 (ae) in the figure is Co-MOF-350 and Mo 100-XPS, C 1s, N 1s, Co 2p and P 2p spectra of CoP@NC; (f) Mo 100 -Mo 3d spectrum of CoP@NC;
[0040] Figure 4 (ab) in the figure is Co-MOF-350, Mo M -CoP@NC and RuO2 oxygen evolution LSV curves and corresponding Tafel slopes; (c) Co-MOF-350 and Mo M -CoP@NC oxygen evolution overpotential bar graph; (d) electrochemical impedance spectroscopy; (e) Mo 100 -CoP@NC in 1 M KOH electrolyte at a constant current density of 10 mA cm -2 (f) is the electrochemical surface area diagram;
[0041] Figure 5 (ab) in the figure is Co-MOF-350, Mo M -CoP@NC and Pt hydrogen evolution LSV curves and corresponding Tafel slopes; (c) Co-MOF-350 and Mo M -CoP@NC hydrogen evolution overpotential bar graph; (d) Mo 100 -CoP@NC in 1 M KOH electrolyte at a constant current density of 10 mA cm -2 Time potential (CP) curve when
[0042] Figure 6 The average catalytic time of the nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst prepared in Example 1, Examples 6 to 14 and Comparative Examples 3 to 5 after 5 cycles of catalytic electrolysis of water;
[0043] Figure 7 It is the catalytic rate of the fifth cycle of catalytic electrolysis of water by the nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst prepared in Example 1, Examples 6 to 14 and Comparative Examples 3 to 5. DETAILED DESCRIPTION
[0045] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.
[0046] Example 1: A method for preparing a nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst, comprising the following steps:
[0047] S1. Preparation of CoMo-MOF
[0048] At room temperature, phosphomolybdic acid and cobalt acetate were mixed and dissolved in DMF at a ratio of 177.02 mg:40 mL. After the dissolution was completed, 328.4 mg of 0.35 mol / L 2-methylimidazole was poured in, stirred for 22 hours, and the product was collected by centrifugation at a speed of 5250 r / min and a centrifugal time of 8 minutes. The product was washed alternately with deionized water and anhydrous ethanol for 3 times, and CoMo-MOF was obtained after drying. The drying temperature was 60 ° C and the drying time was 5.5 hours. The mass ratio of phosphomolybdic acid to cobalt acetate was 100:77.02.
[0049] In this embodiment, the content of phosphomolybdic acid is 100 mg, the content of cobalt acetate is 0.17702 g, DMF is 40 mL, and 2-methylimidazole is 0.3284 g. The product obtained by washing and drying is CoMo-MOF-100;
[0050] S2. Preparation of Mo-CoP
[0051] The CoMo-MOF obtained in step S1 was moved into a tube furnace, and a quartz crucible containing anhydrous sodium hypophosphite was placed on the upstream side of the tube furnace. The temperature was raised to 350°C at a heating rate of 2°C / min under a nitrogen atmosphere and kept for 2 hours, and then cooled to obtain a nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst, recorded as Mo-CoP; the mass ratio of CoMo-MOF to anhydrous sodium hypophosphite was 1:10;
[0052] In this embodiment, the content of CoMo-MOF is 20 mg, the content of anhydrous sodium hypophosphite is 200 mg, and the product after surface functionalization treatment is recorded as Mo100-CoP;
[0053] S3, Application
[0054] The nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst is used in the process of catalyzing the electrolysis of water for hydrogen evolution and oxygen evolution reaction. The application method is: adding the nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst to the water electrolysis system, catalyzing the electrolysis of water molecules at a temperature of 35°C, and monitoring the time taken for complete catalysis to be 4 minutes.
[0055] Example 2: Different from Example 1, in step S1, the concentration of 2-methylimidazole is 0.3 mol / L, the stirring time is 20 h, and the product is centrifuged and collected at a centrifugal speed of 5000 r / min and a centrifugal time of 5 min; the product is washed alternately with deionized water and anhydrous ethanol twice, and dried at a drying temperature of 55°C for 5 h.
[0056] Example 3: Different from Example 1, in step S1, the concentration of 2-methylimidazole is 0.4 mol / L, the stirring time is 24 h, and the product is centrifuged and collected at a centrifugal speed of 5500 r / min and a centrifugal time of 10 min; it is washed alternately with deionized water and anhydrous ethanol for 4 times, and dried at a drying temperature of 65°C for 6 h.
[0057] Example 4: Different from Example 1, in step S2, the temperature is increased to 340°C at a heating rate of 1.5°C / min under an inert atmosphere and kept at this temperature for 2h.
[0058] Example 5: Different from Example 1, in step S2, the temperature is increased to 360°C at a heating rate of 2.5°C / min under an inert atmosphere and kept at this temperature for 2h.
[0059] Example 6: Different from Example 1, the nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst is subjected to surface functionalization treatment;
[0060] The surface functionalization treatment methods are:
[0061] 1) Microporous treatment of carrier: insert the polystyrene microsphere template into a solution containing 0.5% azobisisobutyronitrile and the remainder of vinyl monomer, heat and polymerize at 45°C for 4 hours, then etch with a pore etchant for 32 minutes, wash with ether and dry to obtain a polystyrene particle carrier with three-dimensional pores on the surface;
[0062] The channel etchant comprises, by weight percentage, 32% lime, 13% sodium sulfate, 7% zinc gluconate, 7% divinylbenzene, and the balance tannic acid;
[0063] 2) Composite treatment: a nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst was mixed with tetrahydrofuran in a mass ratio of 17:7 to obtain a mixed solution, and 7 wt.% of hydrogen peroxide was added to the mixed solution for sulfonation for 13 min. After filtration and vacuum drying, the loaded particles were crushed to obtain loaded particles. Finally, the loaded particles were deposited in the three-dimensional pores on the surface of the polystyrene particle carrier by magnetron sputtering under an argon protective atmosphere, and the treated nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst was obtained by homogenization. The vacuum degree of magnetron sputtering was 1.65×10 -1 Pa, working pressure is 18Pa, sputtering power is 60W, argon flow rate is 70sccm, deposition temperature is 250℃, sputtering time is 10min; vacuum drying parameters are: vacuum degree: 115Pa, vacuum temperature is 75℃, drying time is 22min;
[0064] The homogenization method is: first increase the temperature to 75°C at a rate of 2°C / s, then keep the temperature constant for 1.8 hours, apply magnetic field treatment simultaneously during the constant temperature treatment, the magnetic field strength is: 0.6T, the treatment time is: 1.2 hours, then cool down to 48°C at a rate of 0.08°C / s, remove the homogenization furnace and continue to cool to 27°C.
[0065] Embodiment 7: Different from Embodiment 6, the method of surface functionalization treatment is:
[0066] 1) Microporous treatment of carrier: insert the polystyrene microsphere template into a solution containing 0.3% azobisisobutyronitrile and the remainder of vinyl monomer, heat and polymerize at 40°C for 3 hours, then etch with a pore etchant for 25 minutes, wash with ether and dry to obtain a polystyrene particle carrier with three-dimensional pores on the surface.
[0067] Embodiment 8: Different from Embodiment 6, the method of surface functionalization treatment is:
[0068] 1) Microporous treatment of carrier: insert the polystyrene microsphere template into a solution containing 0.7% azobisisobutyronitrile and the remainder of vinyl monomer, heat and polymerize at 50°C for 5 hours, then etch with a pore etchant for 40 minutes, wash with ether and dry to obtain a polystyrene particle carrier with three-dimensional pores on the surface.
[0069] Example 9: Different from Example 6, the channel etchant includes, by mass percentage, 25% lime, 10% sodium sulfate, 5% zinc gluconate, 5% divinylbenzene, and the remainder tannic acid.
[0070] Example 10: Different from Example 6, the channel etchant includes, by mass percentage, 40% lime, 15% sodium sulfate, 10% zinc gluconate, 8% divinylbenzene, and the remainder tannic acid.
[0071] Example 11: Different from Example 6, 2) Composite treatment: The nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst and tetrahydrofuran are mixed in a mass ratio of 5:7 to obtain a mixture, and 5 wt.% of hydrogen peroxide is added to the mixture for sulfonation treatment for 10 min; wherein the vacuum degree of magnetron sputtering is 1.5×10 -1 Pa, working pressure is 15Pa, sputtering power is 40W, argon flow rate is 30sccm, deposition temperature is 200℃, sputtering time is 1min; vacuum drying parameters are: vacuum degree: 100Pa, vacuum temperature is 65℃, drying time is 15min.
[0072] Example 12: Different from Example 6, 2) Composite treatment: The nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst and tetrahydrofuran were mixed in a mass ratio of 30:7 to obtain a mixture, and 10 wt.% of hydrogen peroxide was added to the mixture for sulfonation for 15 min; wherein the vacuum degree of magnetron sputtering was 1.8×10 -1 Pa, working pressure is 20Pa, sputtering power is 80W, argon flow rate is 100sccm, deposition temperature is 300℃, sputtering time is 20min; vacuum drying parameters are: vacuum degree: 133Pa, vacuum temperature is 85℃, drying time is 30min.
[0073] Example 13: Different from Example 6, the method of homogenization treatment is: first increase the temperature to 70°C at a rate of 1°C / s, then keep the temperature constant for 1.5 hours, and simultaneously apply magnetic field treatment during the constant temperature treatment, the magnetic field strength is: 0.3T, the treatment time is: 1 hour, then cool to 45°C at a rate of 0.05°C / s, remove the homogenization furnace and continue to cool to 25°C.
[0074] Example 14: Different from Example 6, the homogenization method is: firstly heating to 80°C at a rate of 3°C / s, and then maintaining the temperature for 2h. During the temperature treatment, a magnetic field is simultaneously applied, the magnetic field strength is 1T, and the treatment time is:
[0075] After 1.5 h, cool to 50 °C at a rate of 0.1 °C / s, remove the homogenizing furnace and continue cooling to 30 °C.
[0076] Experimental Example: The description of this experimental example is based on the scheme described in Example 1, and is intended to illustrate the practical application effect of the present invention.
[0077] 1. Experimental design: In order to illustrate the electrolytic water catalytic performance of the nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst prepared by the present invention, the following experimental groups were designed:
[0078] Blank group: The difference from Example 1 is that (1) 0.3284 g of 2-methylimidazole and 0.17702 g of cobalt acetate were dissolved in 40 mL of DMF at room temperature, and after complete dissolution, the two solutions were quickly mixed, and then stirred at room temperature for 24 h, and the final product was collected by centrifugation, and finally washed and dried to obtain Co-MOF;
[0079] (2) 20 mg of Co-MOF was transferred into the tube furnace, and another quartz crucible containing 200 mg of anhydrous sodium hypophosphite was placed on the upstream side of the tube furnace. The temperature was raised to 350 °C at a rate of 2 °C / min under N2 atmosphere and kept at this temperature for 2 h. After cooling, black powder Co-MOF-350 was obtained.
[0080] Control group 1: This control group is basically the same as Example 1, except that the amount of phosphomolybdic acid in step (1) is 200 mg, and the remaining steps are the same to obtain CoMo-MOF-200 and Mo200-CoP.
[0081] Control group 2: This control group is basically the same as Example 1, except that the amount of phosphomolybdic acid in step (1) is 300 mg, and the remaining steps are the same to obtain CoMo-MOF-300 and Mo300-CoP.
[0082] Control group 3: This control group is basically the same as Example 6, except that silicon dioxide is used as the template.
[0083] Control group 4: This control group is basically the same as Example 6, except that: the channel etchant does not contain divinylbenzene.
[0084] Control group 5: This control group is basically the same as Example 6, except that during the homogenization process, the magnetic field treatment is also applied simultaneously during the heating and cooling processes.
[0085] Example 1, blank group, control group 1 ~ 2 data comparison Figures 1 to 6 As shown, the preparation of Co-MOF does not add phosphomolybdic acid, and its preparation method is the same as that of CoMo-MOF; Co-MOF-350 is the product of Co-MOF calcined at 350°C; MoM-CoP@NC is the product obtained by calcining CoMo-MOF with different phosphomolybdic acid contents; M represents the content of phosphomolybdic acid added, such as Mo100-CoP@NC is the product of adding 100 mg of phosphomolybdic acid.
[0086] Figure 1 By comparing the XRD patterns of Co-MOF and CoMo-MOF-M in (a), we can see that all MOF precursors show similar diffraction patterns, indicating that the addition of phosphomolybdic acid does not change the topological structure of MOF.
[0087] Figure 1 (b) By comparing Co-MOF-350 and Mo M -CoP@NC XRD spectrum shows that the calcined sample is consistent with the spectrum of CoP, indicating that CoP catalyst is prepared. In addition, there is no diffraction peak of molybdenum phosphide, indicating that Mo may be doped in MOF in the form of heteroatoms.
[0088] Figure 2 (ab) are SEM images of Co-MOF and Co-MOF-350, and (cd) are SEM images of CoMo-MOF-100 and Mo100-CoP@NC. It can be seen that the morphology of the sample without phosphomolybdic acid is block-shaped, while the sample with phosphomolybdic acid is bowl-shaped.
[0089] Figure 3 (ae) XPS, C 1s, N 1s, Co 2p, and P 2p spectra of Co-MOF-350 and Mo100-CoP@NC. Among Co 2p, the peak intensities of Co-MOF-350 at 784.11 eV and 800.93 eV belong to Co 2+ , the peak intensities at 781.67eV and 797.41eV belong to Co 3+ The adjacent pairs of two satellite peaks (labeled as "Sat") at 787.74 eV and 804.32 eV belong to Co 2+ In addition, there are double peaks corresponding to Co-P at 778.30eV and 792.99eV. 100 The Co 2p emission spectrum of -CoP@NC also detected a corresponding peak near the same position, but in addition to detecting Co 2+ Except for the two satellite peaks of Co, no other peaks belonging to Co were detected. 2+ This indicates that Mo 100 -Co in CoP@NC is mainly Co 3+ In Co-MOF-350, the three peaks in the N 1s spectrum are pyridinic N, pyrrolic N, and graphitic N, while in Mo 100 In -CoP@NC, the three peaks in the N 1s spectrum are pyrrolic N, graphitic N, and Mo-N centered at 396.66 eV, which indicates that the doping of phosphomolybdic acid changes the form of N species.
[0090] The peak intensities at 230.88eV and 233.93eV in the Mo 3d spectrum belong to Mo 4+ , the peak intensities at 233.18 eV and 236.41 eV belong to Mo 6+ This is partly due to the existence of Mo itself, and partly due to Mo 100 -Binding energy in MoO2 and MoO3 formed on the surface of CoP@NC particles.
[0091] Figure 4 .In OER electrochemical test, Mo 100 -CoP@NC at 10 mA cm -2 The overpotential under the condition is 300mV, which is lower than that of other sample catalysts. Figure 4 c. Figure 4 bShow Mo 100 The Tafel slope of -CoP@NC is also lower than that of other samples, indicating its faster reaction kinetics. Figure 4 In the circuit simulated by the dNyquist diagram, Mo 100-CoP@NC and Mo 200 -CoP@NC exhibits a relatively small charge transfer resistance, indicating a faster electron transfer efficiency. 100 -CoP@NC has good electrochemical durability ( Figure 4 e) Although they have similar C dl value( Figure 4 f), but from the catalytic performance point of view, the performance of the Mo-doped catalyst is better than that of the undoped Mo catalyst. Therefore, the doping of Mo improves the intrinsic activity of the catalyst.
[0092] Figure 5 In the HER electrochemical test, Mo 100 -CoP@NC and Mo 200 -CoP@NC showed obvious HER catalytic activity, which was higher than that of Co-MOF-350 and Mo 300 -CoP@NC, indicating that appropriate amount of Mo doping can improve the HER activity of the catalyst ( Figure 5 a). Figure 5 bShow Mo 100 The Tafel slope of -CoP@NC is also lower than that of other samples, indicating its faster reaction kinetics. -2 When, Mo 100 -CoP@NC and Mo 200 -CoP@NC have overpotentials of 304mV and 299mV respectively. Figure 5 c) and has good stability ( Figure 5 d).
[0093] 2. Investigate the effect of surface functionalization on the electrocatalytic performance of nano-bowl molybdenum-doped metal cobalt phosphide in water electrolysis
[0094] Catalytic stability test method: On the Chenhua 760E electrochemical workstation, constant current electrolysis was used to evaluate the stability of the intermittent water electrolysis catalyst. The electrolyte was 1 mol / L KOH aqueous solution, a graphite rod was used as the counter electrode, a saturated calomel electrode was used as the reference electrode, and a surface-treated nanobowl molybdenum-doped metal cobalt phosphide was fixed with a glassy carbon fixture as the working electrode. The current density was 50 mA / cm 2 , the electrolysis time is 20 minutes, and then stop for 20 minutes, the two are carried out alternately, and the voltage change curve over time is recorded, and the time consumed for complete electrolysis is recorded. The results show that after the surface functionalization treatment of the catalyst, the stability is significantly improved under intermittent electrolysis conditions. After 5 cycles, the average time of complete catalytic electrolysis is taken as the catalytic time.
[0095] Depend on Figure 6-7It can be seen that the use of silica as a template in the preparation of a polystyrene particle carrier with three-dimensional pores in the control group 3 has a weaker effect on the catalyst stability and reusability improvement than the use of polystyrene microspheres in Example 6. This is mainly because the removal of the silica template is not as thorough as that of the polystyrene microsphere template. The residual silica may affect the active sites of the catalyst or gradually fall off during subsequent use, reducing the reusability of the catalyst. In addition, polystyrene microspheres are more likely to be used as templates to control the final carrier pore size and pore connectivity. These pore structure characteristics are crucial to the performance of the catalyst. Inappropriate pore structure may reduce the activity and stability of the catalyst. The presence of divinylbenzene in Example 6 helps maintain the catalyst pores. The integrity of the channel, reducing the collapse of the channel and the deactivation of the active site, thereby improving the stability and reusability of the catalyst, because divinylbenzene has a cross-linking effect, so that the structure of the catalyst carrier can effectively resist the stress under high temperature, pressure or chemical reaction conditions, and when the channel etchant in the control group 4 does not contain divinylbenzene, the channel structure of the catalyst cannot be stabilized and protected to the same extent, resulting in the channel being more likely to change during the catalytic reaction, and the active site being more susceptible to poisoning or deactivation; when the magnetic field treatment in Example 6 is applied only at a constant temperature, a specific magnetic ordered structure or grain refinement can be induced in the catalyst, and it can be kept stable, and the subsequent slow cooling can also reduce the sequence damage to the magnetic particles, providing long-term performance improvement. However, the simultaneous application of magnetic field treatment in the control group 5 during the heating, constant temperature and cooling process will cause thermal expansion and contraction of the material, thereby introducing defects or inhomogeneities in the catalyst, which may gradually accumulate in subsequent catalytic cycles, reduce the stability and activity of the catalyst, and cause the improvement of the stability effect and reusability to be less significant than when only treated at a constant temperature.
[0096] In summary, the surface functionalization treatment proposed in this application can effectively enhance the anti-deactivation and reusability of the nano-bowl-shaped molybdenum-doped metal cobalt phosphide catalyst.
Claims
1. A method for preparing a nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst, characterized in that: The steps include: S1. Preparation of CoMo-MOF At room temperature, phosphomolybdic acid and cobalt acetate were mixed and dissolved in DMF at a ratio of 177.02 mg:40 mL. After the dissolution was completed, 328.4 mg of 0.3-0.4 mol / L 2-methylimidazole was poured in, stirred for 20-24 hours, and the product was collected by centrifugation, and washed alternately with deionized water and anhydrous ethanol for 2-4 times, and dried to obtain CoMo-MOF; S2. Preparation of Mo-CoP The CoMo-MOF obtained in step S1 is moved into a tubular furnace, and a quartz crucible containing anhydrous sodium hypophosphite is placed on the upstream side of the tubular furnace. The temperature is increased to 340-360°C at a heating rate of 1.5-2.5°C / min under an inert atmosphere and kept for 2 hours, and then cooled to obtain a nano-bowl-shaped molybdenum-doped metal cobalt phosphide catalyst, recorded as Mo-CoP.
2. The method for preparing the nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst according to claim 1, characterized in that: In step S1, the mass ratio of phosphomolybdic acid to cobalt acetate is 99-101:76.02-78.
02.
3. The method for preparing the nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst according to claim 1, characterized in that: In step S2, the mass ratio of the CoMo-MOF to anhydrous sodium hypophosphite is 1:
10.
4. The method for preparing the nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst according to claim 1, characterized in that: In step S2, the inert atmosphere is nitrogen or argon.
5. The method for preparing the nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst according to claim 1, characterized in that: In step S1, the centrifugal speed is 5000-10000 r / min, and the centrifugal time is 5-10 min; the drying temperature is 55-65° C., and the drying time is 5-6 h.
6. The method for preparing a nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst according to claim 1, characterized in that: In step S2, the nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst is subjected to surface functionalization treatment; The method of the surface functionalization treatment is: 1) Microporous treatment of carrier: insert the polystyrene microsphere template into a solution containing 0.3-0.7% azobisisobutyronitrile and the remainder of vinyl monomer, heat and polymerize at 40-50°C for 3-5h, then etch with a pore etchant for 25-40min, wash with ether and dry to obtain a polystyrene particle carrier with three-dimensional pores on the surface; 2) Composite treatment: the nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst is mixed with tetrahydrofuran in a mass ratio of 5 to 30:7 to obtain a mixture, and 5 to 10 wt.% of hydrogen peroxide is added to the mixture for sulfonation for 10 to 15 minutes, and the loaded particles are obtained after filtration and vacuum drying, and finally the loaded particles are deposited in the three-dimensional pores on the surface of the polystyrene particle carrier by magnetron sputtering under an argon protective atmosphere, and the treated nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst is obtained by homogenization; wherein the vacuum degree of magnetron sputtering is 1.5×10 -1 ~1.8×10 -1 Pa, working pressure is 15-20Pa, sputtering power is 40-80W, argon flow rate is 30-100sccm, deposition temperature is 200-300℃, sputtering time is 1-20min; vacuum drying parameters are: vacuum degree: 100-133Pa, vacuum temperature is 65-85℃, drying time is 15-30min.
7. The method for preparing a nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst according to claim 6, characterized in that: The channel etchant comprises, by mass percentage, 25-40% of lime, 10-15% of sodium sulfate, 5-10% of zinc gluconate, 5-8% of divinylbenzene, and the balance of tannic acid.
8. The method for preparing a nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst according to claim 7, characterized in that: The homogenization method is: firstly heating to 70-80°C at a rate of 1-3°C / s, then subjecting to constant temperature treatment for 1.5-2h, simultaneously applying magnetic field treatment during the constant temperature treatment, with a magnetic field strength of 0.3-1T and a treatment time of 1-1.5h, then cooling to 45-50°C at a rate of 0.05-0.1°C / s, removing the homogenization furnace and continuing to cool to 25-30°C.
9. Use of a nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst prepared by the method according to any one of claims 1 to 8, characterized in that: The nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst is applied to the process of catalyzing the electrolysis of water to absorb hydrogen and oxygen.
10. The use of a nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst as claimed in claim 9, characterized in that: The method for catalyzing the electrolysis of water using the nano bowl-shaped molybdenum-doped metal cobalt phosphide catalyst is as follows: the electrolyte is a 1 mol / L KOH aqueous solution, a graphite rod is used as a counter electrode, a saturated calomel electrode is used as a reference electrode, and a surface-treated nano bowl-shaped molybdenum-doped metal cobalt phosphide is fixed with a glassy carbon fixture as a working electrode, and the current density is 50 mA / cm 2 The electrolysis time is 20 minutes, and then stop for 20 minutes. The two are performed alternately, and the voltage change curve over time is recorded.
Citation Information
Patent Citations
Preparation method and application of ruthenium-doped cobalt phosphide electrocatalyst
CN112680741B
Cited By
Carbon-coated cobalt-based catalyst, preparation method thereof and application of carbon-coated cobalt-based catalyst in electrolyzed water
CN120060910A
Cobalt molybdenum nitride / cobalt modified nitrogen-doped hollow carbon microspheres and preparation and application thereof
CN120622555A
Cobalt-molybdenum nitride / cobalt-modified nitrogen-doped hollow carbon microspheres and their preparation and application
CN120622555B
Bivalent cobalt phosphide / TiO2 nanocone (at) Ti composite electrode, preparation thereof and application of bivalent cobalt phosphide / TiO2 nanocone (at) Ti composite electrode in organic matter-heavy metal coupling photoelectrocatalysis
CN121158907A